المفارقة اللغوية في معهود الخطاب العربي: دراسة في بنية الدلالة = al-Mufaraqah al-lughawiyah fi ma'hud al-khitab al-'arabi : dirasah biniyat al-dalalah - Ali, Asem Shehadeh Saleh (كلية الآداب واللغات، جامعة قاصدي مرباح، ورقلة، الجزائر،, 2011)
This study is investigating the concept of Irony when applied on analyzing Arabic text, and categorizing its elements. The terminology will explain the deep structure which understood through surface structure. The study will study the concept of irony through the element of Rhetorical Enforcement, deep structure, expectation, Sarcasm. The study may find some elements in the text or more.